DEVELOPMENT OF FBPSS TEACHING MATERIALS AS SEXUAL VIOLENCE EDUCATIONAL MEDIA FOR ELEMENTARY SCHOOL STUDENTS - Laily Saharani; R Rusnilawati (Jurnal Cakrawala Pendas, 2023)
Sexual violence against children is one of the cases that continues every year. This is because public awareness of the importance of education on sexual violence against childrennis still very weak. Not only that, the policies made by the government are still not strong enough to provide a deterrent effect on the perpetrators of crimes. The settlement in this case is very necessary because sexual violence will have an extraordinary impact on victims of violence including depression and death. This study aims to figure out the effectiveness of Personal Safety Skill-based Flipbook media on knowledge and ways to protect themselves from sexual violence in grade 5 students at SDN Tunggulsari II. This study had subjects in the form of 5th grade students at SDN Tunggulsari II which included 10 female students and 8 male students. The type of research method used is Research and Development (R&D) research and development with the ADDIE development model. With this research it is intended that students have knowledge and attitudes about how to protect themselves from sexual violence. so that the number of sexual violence against children does not increase. This is evidenced by the results of the study, namely 57.1 with a percentage of 29% before getting education and an average score of 84.8 with a percentage of 71% after getting Flipbook media education. Kekerasan seksual yang terjadi pada anak merupakan salah satu kasus yang terus mengalami peningkatan setiap tahunnya. Hal ini dikarenakan kesadaran masyarakat terhadap pentingnya edukasi kekerasan seksual terhadap anak masih sangat lemah. Tidak hanya itu saja kebijakan-kebijakan yang dibuat oleh pemerintah masih belum cukup kuat untuk memberikan efek jera pada pelaku tindak kejahatan. Penyelesaian dalam kasus ini sangat diperlukan karena kekerasan seksual akan menimbulkan dampak yang luar biasa pada korban kekerasan diantaranya depresi hingga kematian. Oleh karena itu edukasi kepada anak melalui bahan ajar Flipbook berbasis Personal Safety Skill sangat diperlukan. Penelitian ini mempunyai tujuan untuk mengetahui keefektifan media Flipbook berbasis Personal Safety Skill terhadap pengetahuan dan cara melindungi diri dari kekerasan seksual siswa kelas 5 SDN Tunggulsari II. Penelitian ini mempunyai subyek berupa murid kelas 5 SDN Tunggulsari II yang meliputi 10 siswa perempuan dan 8 siswa laki-laki. Jenis metode penelitian yang digunakan adalah penelitian dan pengembangan Research and Development (R&D) dengan model pengembangan ADDIE. Dengan adanya penelitian ini bertujuan agar siswa memiliki pengetahuan dan sikap tentang bagaimana cara untuk melindungi diri dari kekerasan seksual. sehingga angka kekerasan seksual pada anak tidak mengalami peningkatan. Hal ini dibuktikan dengan hasil penelitian yaitu 57,1 dengan presentase 29% sebelum mendapatkan edukasi dan rata-rata skor 84,8 dengan presentase 71% setelah mendapatkan edukasi media Flipbook.